Influence Tiktok Advertisement To Decision Hotel Accommodation Purchases Among The Zennial Generation - Nurhafiza, Emtiqa Nurhafiza; Sinambela, Fitriana Aidnilla; Fahlevi, Renza (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to test the influence of emotions, entertainment, and information in TikTok Advertisement on consumer behavior and hotel purchasing decisions among the Zennial Generation. The results of testing using SmartPLS software show that emotions do not has a significant effect on purchasing decisions (β = 0.041, t-statistic = 0.919, p = 0.358), but ... significant to behavior consumer (β = 0.158, t-statistic = 2,661, p = 0.008). Entertainment also has no significant effect on purchasing decisions (β = 0.100, t-statistic = 1.097, p = 0.273), but has a significant effect on consumer behavior (β = 0.215, t-statistic = 2.326, p = 0.020). Information is proven to have a significant effect on consumer behavior (β = 0.608, t-statistic = 7.069, p = 0.000) and purchasing decisions through consumer behavior (β = 0.479, t-statistic = 4.614, p = 0.000). In addition, there is a significant influence of emotional (β = 0.124, t-statistic = 2.564, p = 0.010) and entertainment (β = 0.169, t-statistic = 2.050, p = 0.040) on purchasing decisions through consumer behavior. Overall, this study shows that factors in TikTok Advertisement can influence consumer behavior and hotel purchasing decisions in the Zennial Generation, with information as the most dominant factor.